The Impact of Threats on the Level of Security of the Process of Supply of Petroleum Products to Customers - Paweł KLER (Communications of International Proceedings, 2021)
The article focuses on identifying sources of threats affecting the level of security of petroleum product supply processes, taking into account the COVID-19 pandemic. Within the elements of the petroleum supply chain (PSC), the characteristics and stages of implementation of this process have been presented. The process approach allows for the application of critical thinking skills of all parties of the organization in order to use their intellectual potential in making specific decisions. Different levels of approach, which should be subject to critical thinking of each logistician, have been distinguished. On the basis of the collected data, a risk identification analysis has been carried out in relation to the petroleum product supply processes based on literature as well as on own observations and experiences. The author puts forward a thesis that in the coming years the theory and practice of managing the petroleum product supply chain will have to react even more dynamically and effectively to crisis situations and their negative effects.
Keywords: Threats; processes; supplies; petroleum products; logistics